Documentation of wild edible minor fruits used by the local people of Barishal, Bangladesh with emphasis on traditional medicinal values - Islam, ATM Rafiqul; Das, SK; Alam, MF; Rahman, AHMM (Journal of Bio-Science, 2019)
The present investigation has been conducted for identification, documentation and exploration of wild edible fruit producing plant species and traditional medicinal uses of these fruits by local peoples from 14 villages of 7 upazila of Barisal district. A total of 43 wild edible fruit producing plant species belonging to 33 genera under 23 families have been recorded. For each species scientific, local and English name, habit, fruiting time and traditional medicinal uses of these fruits have been presented. Among the identified species Polyalthia suberosa Roxb., Flacourtia indica (Burm.f.) Merr., Flacourtia jangomas (Lour.) Rausch., Dimocarpus longan Lour., were recorded from the study area as new findings. Moreover, Flacourtia indica (Burm.f.) Merr., Flacourtia jangomas (Lour.) Rausch., Dimocarpus longan Lour., Polyalthia suberosa Roxb., Syzygium jambos L., Lepisanthes senegalensis (Poir.) Leenhouts., Lepisanthes rubiginosa (Roxb.) Leenh., were identified as rare species and currently they are endangered in their natural habitat. The findings of the research indicate that, there has a great pharmacological value of wild edible fruits for discovering new drugs and medicines. J. bio-sci. 27: 69-81, 2019